Wawasan Hadis Tentang Shalat Istisqa - Munadi, Radhie (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2024)
This article discusses the traditions of Istisqa prayer. The definition of istisqa' prayer, the ruling of istisqa' prayer, and the traditions of istisqa' prayer, especially those related to the procedure and timing of istisqa' prayer, will be the main points of discussion in this article. Therefore, it is necessary to explain these matters so as not to confuse the issue of Istisqa's prayer. The study of this issue was conducted through a literature review of the traditions of the Prophet Muhammad PBUH. The conclusion is that the istisqa prayer is a prayer asking for rain whose procedures and time of performance were carried out by the Prophet Muhammad PBUH in various situations according to the conditions faced. As for the ruling of the Istisqa prayer, there are different views among scholars. Some have ruled it sunnah, and others have ruled it obligatory. However, it should be noted that, in general, the traditions of prayer are indicated to be temporal.